Full‐current‐based directional pilot protection for VSC‐DC distribution systems. Issue 16 (26th July 2019) - Li, Meng; Jia, Ke; Bi, Tianshu; Wang, Congbo; Zhu, Rui; Yang, Qixun
Abstract : Line protection is of great challenge for Voltage Source Converter‐Direct Current (VSC‐DC) distribution systems because the protection scheme must selectively identify the fault section as fast as possible. This study proposes a full‐current‐based directional pilot protection to meet the above requirements. The proposed protection utilises the full‐current (the measured current). The theoretical analyses, which have considered the influence of the VSC blocking, have proved that the full‐current has a certain direction during a pole‐to‐pole short‐circuit fault. Therefore, the protection is robust to the non‐linearity of the DC system. The theoretical analyses have also pointed out that the protection is immune to the line‐distributed capacitance. Both experimental and simulation results have demonstrated the analyses. The proposed protection can trip in <2 ms at a 1.6 kHz sampling rate in the experiments and within 1 ms at a 10 kHz sampling rate in the simulations. It can also correctly operate with 20 dB white noise and 20 Ω fault resistance. There is also no strict synchronisation requirement for the measurements of both the terminals. These features make the protection feasible for industry application.